Cannabis use in Attention – Deficit/Hyperactivity Disorder (ADHD): A scoping review. (January 2023) - Francisco, Ana Paula; Lethbridge, Grace; Patterson, Beth; Goldman Bergmann, Carolina; Van Ameringen, Michael
Abstract: Introduction: Treatments for Adult ADHD include stimulants, two non-stimulant medications, as well as cognitive-behavioral therapy (CBT). These pharmacological agents are often associated with side effects, contributing to poor treatment adherence. Patients with ADHD have regularly stated that cannabis has helped improve their ADHD symptoms; however, scientific literature describing the effects of cannabis on symptoms of ADHD is scarce. Methods: We systematically searched MEDLINE, EMBASE, EMCARE, PsycINFO, Web of Science, Cochrane Library, and Clinicaltrials.gov . The searches included all publications in English up to June 27, 2022. We included both experimental and observational studies that assessed the effect of cannabis on ADHD symptomatology and neuropsychiatric outcomes. To synthesize our current understanding of the potential effects of cannabis use on ADHD symptoms and pathophysiology, and the effects of ADHD on cannabis use, data was extracted from each study regarding the characteristics of its population, methods used to assess both cannabis consumption and ADHD symptoms, and key findings. Results: Our scoping review included a total of 39 studies. Only one study employed a randomized and placebo-controlled design to directly measure the effect of cannabis on ADHD, and no significant effect was observed for the study's primary outcome, the QbTest (Est = −0.17, 95% CI -0.40 to 0.07, p = 0.16). Most of the literature consists of cross-sectional studies that evaluate the association between ADHD severity and cannabis use. 15 studies addressed the neuropsychiatric effects of cannabis on ADHD by employing either a battery of neuropsychiatric tests or neuroimaging. The concentration and amount of THC and CBD used were not well measured in most of the studies. Although some studies indicated that cannabis improved ADHD symptoms, most studies indicated it worsened or had no effect on ADHD symptoms. Conclusions: Given the current evidence, cannabis is not recommended for people with ADHD. Limitations of the literature include the absence of objective measurements for cannabis exposure and ADHD symptoms, heterogenous definitions, oversampling, and small sample sizes. Highlights: Only one RCT was identified, which showed no significant effect of cannabis on ADHD. ADHD patients anecdotally report improvement in their symptoms with cannabis. Evidence from self-reports of recreational cannabis users on the impact of cannabis on their attention is extremely low. The isolated effect of CBD on ADHD symptoms and pathophysiology is not well-known. There is not enough evidence to recommend cannabis as a treatment for ADHD.